A decision-making support for supplier selection and inventory optimisation considering price discount and fuzzy parameters via piecewise-objective mixed-integer programming. (10th October 2022) - Sutrisno, S.; Widowati, W.; Sunarsih, S.; Arreeras, Tosporn; Syukur, Muhammad
In this paper, we propose a piecewise-objective mixed-integer optimisation model as a decision-making support to solve integrated supplier selection and inventory optimisation, considering price discount and fuzzy parameters. The mathematical model was formulated based on minimising the total operational costs whereas the constraint functions were formulated based on situations that should be met, such as satisfying demand and supplier capacity limits. Numerical experiments were performed with randomly generated data to evaluate the model and to illustrate how the optimal decision was made. Results showed that the model successfully solved the given problem, and the optimal decision was derived, i.e., the optimal product amount of each product type that should be purchased to each supplier and the product amount of each product type that should be stored in the warehouse for each observation time period. This concluded that the proposed model can be used by decision-makers to solve their supply chain problems.